2017
DOI: 10.1186/s12879-017-2447-0
|View full text |Cite
|
Sign up to set email alerts
|

Total delay in treatment among tuberculous meningitis patients in China: a retrospective cohort study

Abstract: BackgroundCurrently, there is limited data on the risk factors associated with treatment delay in tuberculous meningitis (TBM). This study aimed to assess the duration of delay in the treatment TBM and to investigate its determinants.MethodsDuring the period from September 2009 to February 2016, a retrospective cohort study of consecutive TBM patients admitted to our hospital was conducted to determine the risk factors associated with treatment delay in TBM. Treatment delay duration was defined as the time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
3
20
5
Order By: Relevance
“…In addition, children with TBM during hospitalization showed varying degrees of anti-tuberculosis drug-induced hyperuricemia (23.8%) and hepatotoxicity (14.3%). These frequent adverse events associated with TB treatment ratio were higher in the current study compared to previous ones [5,16]. This could be because the development of liver and kidney function in children is not perfect, and their ability to remove drugs is poor, which makes them more sensitive to drug reactions and more prone to adverse reactions compared to young adults.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, children with TBM during hospitalization showed varying degrees of anti-tuberculosis drug-induced hyperuricemia (23.8%) and hepatotoxicity (14.3%). These frequent adverse events associated with TB treatment ratio were higher in the current study compared to previous ones [5,16]. This could be because the development of liver and kidney function in children is not perfect, and their ability to remove drugs is poor, which makes them more sensitive to drug reactions and more prone to adverse reactions compared to young adults.…”
Section: Discussioncontrasting
confidence: 58%
“…It may that smear positive PTB patients were easier to be diagnosed for bacteriological evidence, more likely to be infectious and NTP paid more attention to them than TB pleurisy patients. Previously treated patients had significantly higher treatment initiation delay which could be because of their previous bad experience of TB treatment, similar as reported elsewhere/before in India and China [13,32]. Patient registered in referral hospital had significant higher treatment initiation delay after diagnosis due to procedural and interest reasons [44].…”
Section: Predictors Of Health System Delaymentioning
confidence: 53%
“…The median total delay (22 days) and patient delay (16 days) were quite shorter compared to studies in other high TB burden countries [28,30]. Migrant TB patients received proper diagnosis and management within very short duration of having any symptom of TB and almost immediately after visiting a health facility in China [31] as other general populations [32]. We speculate that this was due to four important reasons.…”
Section: Short Patient and Health System Delaysmentioning
confidence: 81%
“…Located in the southwest hinterland of the Chinese mainland, Sichuan province, the gateway to the southwest of China, is a big multi-ethnic family with the second largest Tibetan region in China. Although the Chinese government has strengthened TB control in minority areas in recent years and achieved some success, childhood TBM still remains a neglected field [3][4]. WHO and numerous studies have been reported that BCG vaccination can protect children from the severe types of TB such as TB meningitis and miliary TB [5][6].…”
Section: Discussionmentioning
confidence: 99%